Is CT scan a predictor of instability in recurrent dislocation shoulder? - K.P. Shijith (Chinese Journal of Traumatology, 2019)
Purpose: Glenoid bone defect and the defect on the posterior-superior surface of the humerus “Hill-Sachs lesion” are the commonly seen bony lesions in patients with recurrent dislocation shoulder. Computed tomography (CT) scan is considered as the best option in assessing the bony defects in the recurrent dislocation shoulder. The aim of this study was to assess the clinical and radiological co-relation in the patients with recurrent dislocation shoulder. Methods: Forty-four patients of recurrent dislocation shoulder who were evaluated between January 2015 and December 2017 at a tertiary care center, clinically and radiologically using CT scan and meeting the inclusion criteria, were included. The correlation between the clinical history of the number of dislocations and the bone loss using CT scan was evaluated. Two sided statistical tests were performed at a significance level of α = 0.05. The analysis was conducted using IBM SPSS STATISTICS (version 22.0). Results: All the patients were male with mean age of 25.95 (SD ± 4.2) years were evaluated. Twenty-four patients sustained injury in sporting activities while 20 patients sustained injury in training. There were an average of 4.68 (SD ± 3.1, range 2–15, median 3) episodes of dislocation. Forty-one patients had the glenoid bone loss while 40 had the Hill-Sachs lesions. The mean glenoid width defect was 10.80% (range 0–27%) while the mean Hill-Sachs defect was 14.27 mm (range 0–26.6 mm). The mean area of bone loss of the glenoid surface was 10.81% (range 0–22.4%). The lesions were on track in 34 patients and off track in 10 patients. Conclusions: CT scan of the shoulder joint is an effective method for assessing the amount of bone loss. The number of dislocations are correlated significantly with off-track lesions and the amount of bone loss on the glenoid and Hill-Sachs lesion. The glenoid width bone loss of more than 9.80% or Hill-Sachs defect of more than 14.80 mm are the critical defects after which the frequency of dislocations increases. Keywords: Shoulder joint, Recurrent dislocation, Hill-Sachs lesion